Analisis Penanganan Operasional Baggage Handling System Dalam Meningkatkan Keamanan Bagasi Penumpang Di Bandar Udara Sultan Muhammad Kaharuddin Sumbawa Nusa Tenggara Barat - Nia Andriani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Baggage handling has a very important role in supporting the safety and comfort of passengers while traveling by airplane, then processing the baggage according to existing procedures until the baggage arrives at its destination using the same aircraft as the passenger. To find out the handling of BHS in improving passenger baggage security, as well as solutions in handling BHS operational operations so as to improve passenger baggage security, baggage handling at Operations (BHS) at Sultan Muhammad Kaharuddin Airport, Sumbawa. It is carried out through a system that has several gradual processes. The process begins when passengers check-in and hand over their baggage to the check-in officer, then the baggage is given a special coded label as baggage identity. Then the baggage will enter the system with the conveyor belt as the path, then the baggage will go through several stages or levels of security and several stages of automatic sorting. After all stages of the process, both at the security level check and at the baggage sorting stage, are deemed safe, the baggage will go to the make up area of each airline or to the destination on the baggage identity tag which the system has read during the sorting process. Each stage of operations (BHS) is able to guarantee the safety and movement of the baggage is always maintained and monitored through a system that is connected to one another. The existence of a connection from the system guarantees that the baggage is in a safe condition, both the contents and physical condition of the baggage and the baggage handling process becomes faster and more efficient in terms of time and effort.